PENGARUH KUALITAS LAYANAN, HARGA, PROMOSI TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING - Agus Priadi; Aloysius Rangga Aditya Nalendra; Slamet Heri Winarno (KREATIF : Jurnal Ilmiah Prodi Manajemen Universitas Pamulang, 2022)
This research is a qualitative method with the use of a causal approach to see the cause and effect relationship between variables, where the variables used are variables that give influence (independent) and other variables are dependent variables, and the variable involving intervention is a variable. which gives an indirect effect. This study examines E-commerce Shopee food with variables of price, service quality, giving promotion. They had effect to consumer satisfaction and customer loyalty. a sample of 64 respondents. The sampling technique used is purposive sampling. The data analysis technique used is path analysis which is useful in knowing the relationship between each variable. and consumer loyalty.